2014
DOI: 10.1177/0886109914537490
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Relationships

Abstract: Research has demonstrated the importance of supportive relationships and social networks to prisoners' psychosocial outcomes, especially for women. Understanding how these relationships are constructed, negotiated, and sustained is, therefore, critical for social workers and other professionals who work with incarcerated and formerly incarcerated clients, and/or their family and friends. This article analyzes formerly incarcerated women's narratives about prison foodways, demonstrating the centrality of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Many women mentioned that, when at homes, they would cook food, which they thought had beneficial effect on health. A similar idea has been found in earlier studies that showed that perceptions toward food in prisons also redefine how people "read" their bodies and reconstruct notions of "good" and "healthy" (Smith, 2002(Smith, , 2009Smoyer, 2015aSmoyer, , 2015b. In the prisons under study, food was often assessed in terms of nutritional and medicinal values.…”
Section: Experiencing Food In Relation To Healthsupporting
confidence: 62%
“…Many women mentioned that, when at homes, they would cook food, which they thought had beneficial effect on health. A similar idea has been found in earlier studies that showed that perceptions toward food in prisons also redefine how people "read" their bodies and reconstruct notions of "good" and "healthy" (Smith, 2002(Smith, , 2009Smoyer, 2015aSmoyer, , 2015b. In the prisons under study, food was often assessed in terms of nutritional and medicinal values.…”
Section: Experiencing Food In Relation To Healthsupporting
confidence: 62%
“…Inmates who identify less with criminalistic labels and more with pro-social identities are more well-adjusted in general (Cochran, 2012; Rowe, 2011; Smoyer & Minke, 2015). Because food is such a powerful avenue to access and practice identity, the activity of creating food behind bars may lead to safer jails, more effective re-entry experiences, and improved morale and well-being (Smoyer, 2014, 2015; Stevens, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation should be noted in the various rationales for preparing one's own food behind bars. Research suggests in-cell cooking or baking is often undertaken for status, to combat boredom, to join social networks, or to create food that is tasty (see Cate, 2008;Rouhan, 2016;Smoyer, 2014Smoyer, , 2015. In addition, some individuals may have previous baking abilities or are interested in learning a new skill.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations